2008
DOI: 10.1038/nnano.2008.162
|View full text |Cite
|
Sign up to set email alerts
|

Imaging nanoparticles in cells by nanomechanical holography

Abstract: Nanomaterials have potential medical applications, for example in the area of drug delivery, and their possible adverse effects and cytotoxicity are curently receiving attention. Inhalation of nanoparticles is of great concern, because nanoparticles can be easily aerosolized. Imaging techniques that can visualize local populations of nanoparticles at nanometre resolution within the structures of cells are therefore important. Here we show that cells obtained from mice exposed to single-walled carbon nanohorns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 28 publications
2
119
0
Order By: Relevance
“…To illustrate the importance of beating in heterodyne measurements, we use the example of heterodyne force microscopy (HFM) [8][9][10] , as it represents a model system with a highly nonlinear mixing element (much higher order than quadratic). HFM enables the non-destructive imaging below a surface with nanometre resolution using an atomic force microscope [11][12][13][14][15][16][17][18][19] . The typical excitation scheme is sketched in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the importance of beating in heterodyne measurements, we use the example of heterodyne force microscopy (HFM) [8][9][10] , as it represents a model system with a highly nonlinear mixing element (much higher order than quadratic). HFM enables the non-destructive imaging below a surface with nanometre resolution using an atomic force microscope [11][12][13][14][15][16][17][18][19] . The typical excitation scheme is sketched in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous mechanical and chemical mapping have been obtained using mode synthesizing atomic force microscopy (MSAFM) (Tetard et al, 2008(Tetard et al, , 2010(Tetard et al, , 2011 and the additional spectroscopic capabilities of hybrid photonic nanomechanical force microscopy (HPFM) (Tetard et al, 2015;Farahi et al, 2017). Capitalizing on the nonlinear probe-sample forces, microscopy with MSAFM offers a way to image soft samples and probe nanostructures that are below their surfaces (subsurface imaging).…”
Section: Mode Synthesizing Atomic Force Microscopy (Msafm) and Hybridmentioning
confidence: 99%
“…In both MSAFM and HPFM, the specific type of driving of the sample and the probe is selected based upon the specific application and the need for accessing subsurface, topographical, or chemical information. In general, both the probe and sample can be driven (Tetard et al, 2008) via any number and combination of waveform. In either case, the probe-sample interaction via the van der Waals force allows for synthesis of new oscillation modes in the system.…”
Section: Mode Synthesizing Atomic Force Microscopy (Msafm) and Hybridmentioning
confidence: 99%
“…In fact, when materials are embedded deeply from the sample surface (> 1 μm; much shorter than the wavelength of ultrasounds with a few MHz frequency), no sub-surface image appears on the acoustic phase image (unpublished data). It has been demonstrated that SNFUH has a capability of imaging artificial solid particles introduced in cells [190]. However, the live cell membranes are extremely soft, and therefore, it is likely that the cantilever tip deeply pushes the cell membrane to 29 sense the solid particles.…”
Section: Scannermentioning
confidence: 99%